(untitled) (Research, Society and Development, 2022)
This article approaches consumer vulnerability and the Covid-19 pandemic in relation to rights and protections in case of cancellation of concerts and artistic performances in Brazilian legislation. The pandemic of the new Coronavirus (Covid-19) has caused devastating impacts on global health, affecting not only consumers, but the entire consumption chain, in relation to cancellations of shows, artistic presentations reaching the consumer area on a global scale. An approach was made to the supplier-consumer legal relationship based on the principles of law, in particular consumer law, which is the Brazilian legislative protection, with a view to balance in consumer relations in times of pandemic. For that, the methodology of bibliographic research is used, which consists of reading the main authors of the law that deal with this subject and in the comparison of their positions and doctrinal contribution.